Exploring the Use of Collaborative Learning Techniques to Enhance Interpersonal Intelligence - Janneker, Shaylan (The IIE, 2017)
The research project explores the effects of collaborative teaching and learning methods have upon interpersonal intelligence, primarily focusing on the implementation of tasks and activities in a participatory environment Research falls under the paradigm of post positivism, as the intention is to explore and initiate a degree of intended change amongst respondents. The research is quantitative in nature, having data in the form of responses generated through survey-based questionnaires using Likert scale based questioning techniques. Findings reflect that respondents share generally positive sentiments towards the activities at hand, often agreeing with the notion that collaborative learning techniques provided a better understanding of both the curriculum at hand and towards others. These findings in conjunction with an analysis substantiates the notions of theorists that collaborative learning techniques allows for an enhancement of interpersonal intelligence.
Keywords: Collaborative learning; Interpersonal intelligence